The impact of IFRS 16 on the lessees’ valuation: experimental evidence of the impact of lease accounting principles on analysts’ assessment of lessees’ financial position and performance - Ricci Junior, Carlos Alberto (2019)
Purpose: Until 1983 companies have not recognized any leased asset or any lease liability. From 1984 until 2018, while the IAS 17 was effective, companies recognized only finance lease assets and the respective liability. Since 2019, companies implemented IFRS 16, thus began to recognize virtually all lease assets and liabilities. Such change affects the measurement of income; hence also impact financial ratios such as liquidity, leverage and profitability. Design/Methodology: Based on experimental evidences, we investigate how analysts react to the recent change in accounting policy promoted by IFRS 16. Findings: Results show that analysts tend to value differently companies under different lease accounting rules, calculating higher EBITDA and higher Net Debt when IFRS16 is applied. Research limitations: The Colombian survey did not collect any demographical data. The Brazilian experiment collected such information but was limited to fifty-two qualified respondents. Practical implications: Many studies have been conducted to predict how financial ratios should change after IFRS 16 implementation, but none to predict how market will value companies. Social implications: Analysts do not behave as corporate finance literature predicts; i.e., analysts may not adjust target firms’ financial reports before calculating the ratios and reaching conclusions about their financial performance and position. Hence, the mandatory accounting police change required by the IFRS 16 is a valuable decision aid to financial analysts. Originality: Prior research on the recent lease accounting policy change has focused on archival data and aims to assess the impact of IFRS on firms’ financial performance and financial position. However, there is a lack in literature on the effect of such mandatory accounting policy change on analysts’ reaction. This study fills such gap.